2007
DOI: 10.58809/mesc2666
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Test of Stewardship Theory

Abstract: This study tests the model of Davis, Schoorman, and Donaldson (1997) that proposed determinants of a company’s governance structure. In particular, we focus on the stewardship theory aspects of the model and its ability to predict the presence of a stewardship-orientation CEO at publicly listed U.S. companies. Using survey based data obtained from CEOs and directors of 100 companies in a match-pair design, we identified three variables that predicted the occurrence of stewardship-oriented behaviors by the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Board demographic diversity can enhance stewardship by improving a firm's decision-making process by means of diverse views, experiences and sensitiveness (Nguyen et al, 2021), thus broadening stewardship to benefit a wider range of stakeholders and the environment. Under this view, a longer board tenure reduces board's discussions and may uniform views and opinions inside the board (Davis et al, 2007), moderating the positive effect of demographic diversity on environmental performance. In family firms this implies an alignment to the owning family priorities and translates into a lower propensity to entrepreneurial risk (Huybrechts et al, 2013) and the pursuit of environmentally risky strategies.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Board demographic diversity can enhance stewardship by improving a firm's decision-making process by means of diverse views, experiences and sensitiveness (Nguyen et al, 2021), thus broadening stewardship to benefit a wider range of stakeholders and the environment. Under this view, a longer board tenure reduces board's discussions and may uniform views and opinions inside the board (Davis et al, 2007), moderating the positive effect of demographic diversity on environmental performance. In family firms this implies an alignment to the owning family priorities and translates into a lower propensity to entrepreneurial risk (Huybrechts et al, 2013) and the pursuit of environmentally risky strategies.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Stewardship theory provides a normative perspective of corporate governance in which stewards are intrinsically motivated to serve corporate stakeholders (Davis et al, 2007;Davis et al, 1997). Furthermore, the theory indicates that stewards in organisations with competing stakeholder objectives are motivated to make decisions that are in the best interests of the group (Davis et al, 1997).…”
Section: Stewardship Theory and The Role Of The Boardmentioning
confidence: 99%
“…Stewardship theory provides a normative perspective of corporate governance in which stewards are intrinsically motivated to serve corporate stakeholders (Davis et al. , 2007; Davis et al ., 1997).…”
Section: Background and Research Questionmentioning
confidence: 99%
“…Stewardship theory highlights the board's duty as stewards of the bank, with a responsibility to act in the best interests of all stakeholders, including customers, staff, shareholders, and the larger community (Donaldson and Davis, 1989). An empirical test of stewardship theory (Davis et al, 2007) suggests that when principals and agents are aligned, it is because of some sort of psychological contract or because they have a very close relationship in which the agent acts in the best interests of the community and the firm and its shareholders. Successful board meetings can assist the board in fulfilling this obligation by fostering openness, accountability, and ethical behavior.…”
Section: Theoretical Literaturementioning
confidence: 99%
“…Consequently, it can be argued that larger boards are more advantageous for a significant number of financial firms. A study found that banks with larger boards tended to have lower risk-taking and higher profitability (Davis et al 2007). Additionally, having a more diverse board with members who bring different skills and perspectives has been found to improve bank performance (Adams and Ferreira, 2009).…”
Section: Berger Et Al (mentioning
confidence: 99%